2023
DOI: 10.3389/fcvm.2023.1160231
|View full text |Cite
|
Sign up to set email alerts
|

Determination of lethal electric field threshold for pulsed field ablation in ex vivo perfused porcine and human hearts

Abstract: IntroductionPulsed field ablation is an emerging modality for catheter-based cardiac ablation. The main mechanism of action is irreversible electroporation (IRE), a threshold-based phenomenon in which cells die after exposure to intense pulsed electric fields. Lethal electric field threshold for IRE is a tissue property that determines treatment feasibility and enables the development of new devices and therapeutic applications, but it is greatly dependent on the number of pulses and their duration.MethodsIn t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…This curated set of pulse parameters can subsequently undergo validation on a limited number of animal models. Furthermore, when coupled with numerical modeling that incorporates the specific electrode geometry and anatomical target site, the user will be empowered to estimate alterations in ablation volume ( Kos et al, 2023 ), corresponding to changes in pulse parameters, utilizing EFTs obtained from this tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This curated set of pulse parameters can subsequently undergo validation on a limited number of animal models. Furthermore, when coupled with numerical modeling that incorporates the specific electrode geometry and anatomical target site, the user will be empowered to estimate alterations in ablation volume ( Kos et al, 2023 ), corresponding to changes in pulse parameters, utilizing EFTs obtained from this tool.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, limited data are available regarding the impact of waveform parameter selection on cardiac lesion formation, largely due to medical device developers with proprietary waveform characteristics leading the PFA development. Only a handful of nonclinical studies have published the waveform parameters used ( Stewart et al, 2019 ; van Es et al, 2019 ; Caluori et al, 2020 ; Loh et al, 2020 ), or investigated the impact of these parameters on treatment effectiveness in diverse animal models ( Zager et al, 2016 ; Heller et al, 2021 ; Yavin et al, 2021 ; García-Sánchez et al, 2022 ; Kos et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…This also means that the area of ablation by irreversible electroporation will be the smallest, surrounded by reversible electroporation, and affecting/stimulating the nerves passing through the surrounding zone (Figure 10). It is important to note that the spatial distribution of the electric field depends on the biophysical properties of the cardiac tissue, including the inhomogeneity and anisotropy of electric (i.e., conductivity and dielectricity) attributes, as well as on the electrode's shape, i.e., the catheter design, and whether the pulses are delivered in a unipolar or bipolar fashion [57,58]. During a PFA treatment using specific waveforms, the electrical pulses are delivered to a treatment site using an ablation therapy delivery device composed of a pulse generator and a catheter.…”
Section: Discussionmentioning
confidence: 99%
“…PFA is based on irreversible electroporation technology, which applies electric field intensity above the lethal electric field threshold for cell death to disrupt cell membranes and induce cell death. The lethal electric field threshold for cell death not only depends on tissue type but also on pulse parameters and other factors ( 7 ). Recent in vitro studies have only partially confirmed the tissue specificity of PFA.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from skeletal muscle ( 8 ), myocardial cells have a lower lethal electric field threshold for cell death, especially compared to esophageal smooth muscle cells and phrenic nerve cells. Myocardial cells are more susceptible to electroporation injury, with a lower threshold for cell death than other tissues ( 7 , 9 , 10 ). This selectivity is a fundamental cellular characteristic ( 11 ).…”
Section: Introductionmentioning
confidence: 99%